(untitled) (مجلة البحوث الأكاديمية, 2021)
In this study, the top 10 web application security vulnerabilities published by OWASP, the sources of the vulnerabilities and the security solutions used to prevent attacks that exploit these vulnerabilities were investigated, the precautions that can be taken against the attacks that can be carried out using these vulnerabilities were evaluated in terms of usage areas, platform-independence, working logic and efficiency have been compared. In line with the information and findings obtained, suggestions on what kind of security solution should be taken and preferred against which types of attacks, and solutions for increasing awareness and web application security were presented.